2013
DOI: 10.1371/journal.pone.0071498
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Naive and Increased Memory CD4+ T Cells Are Associated with Subclinical Atherosclerosis: The Multi-Ethnic Study of Atherosclerosis

Abstract: BackgroundAdaptive immunity has been implicated in atherosclerosis in animal models and small clinical studies. Whether chronic immune activation is associated with atherosclerosis in otherwise healthy individuals remains underexplored. We hypothesized that activation of adaptive immune responses, as reflected by higher proportions of circulating CD4+ memory cells and lower proportions of naive cells, would be associated with subclinical atherosclerosis.Methods and FindingsWe examined cross-sectional relations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
64
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 81 publications
(78 citation statements)
references
References 49 publications
13
64
0
1
Order By: Relevance
“…Previous studies also have demonstrated that significant reduction of Treg cells in NSTACS patients resulted both from the reduced export of RTE-Treg and accelerated apoptosis of Treg in the periphery 21) . In this study, the result that reduced sj-TREC copy number from total T lymphocytes in CAD patients was consistent with the previously reported reduced proportion of naïve T cells 13) . And the proportion of naïve T cells was ever used to reflect thymic output 48) .…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Previous studies also have demonstrated that significant reduction of Treg cells in NSTACS patients resulted both from the reduced export of RTE-Treg and accelerated apoptosis of Treg in the periphery 21) . In this study, the result that reduced sj-TREC copy number from total T lymphocytes in CAD patients was consistent with the previously reported reduced proportion of naïve T cells 13) . And the proportion of naïve T cells was ever used to reflect thymic output 48) .…”
Section: Discussionsupporting
confidence: 93%
“…Aging is associated with an alteration of the proportion of naïve T and effector memory T cells (Tem) in periphery 54) , with Tem expanding to maintain T cell homeostasis. Previous investigations have also reported a similar phenomenon in human and animal models of atherosclerosis 13,55) . Numerous factors have been involved in the immune system imbalance, the most important being thymus involution and the resultant decreased output of naïve T cells 54) .…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…There is a body of evidence that in individuals over the age of 65 years there are changes to the immune response that increase the rates of morbidity and mortality in response to infection and autoimmune disease (38,39). Analysis of a number of large population cohorts recruited for cancer, dementia, and nutritional studies in the UK and the United States has shown a significant association between CMV seropositivity and mortality from cardiovascular-related disease (40)(41)(42)(43). Despite these observations, older CMV-seropositive individuals do not appear to suffer from overt HCMV disease from reactivating virus or superinfection, suggesting that the HCMV-specific T cells retain the ability to control the virus (44).…”
mentioning
confidence: 99%
“…In contrast to Th 1, Tregs can suppress inflammatory responses by various mechanisms (182)(183)(184)(185)(186). Tregs serve to maintain immunological tolerance and suppress effector T cell responses (187). The atheroprotective effect of Tregs on atherosclerosis has been reported in both a mouse model and a human study (188,189).…”
Section: Inflammationmentioning
confidence: 99%